The Effect of Group Investigation Learning Model on Social Studies Learning Outcomes of Class IV SDN SUKO 1 SIDOARJO: Pengaruh Model Pembelajaran Group Investigation Terhadap Hasil Belajar IPS Kelas IV SDN SUKO 1 SIDOARJO - Afifah, Nur; Afandi, Rifki (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study is to determine the effect of Group Investigation learning model toward IPS (social studies) outcome in grade IV SDN Suko 1 Sidoarjo. This study used the pre-experimental design model with a one-group pretest-posttest design. The result shows that the T-test calculation was 19,31 ≥ t-table 1,717, which means that Ho was rejected and Ha was accepted. It means there is an influence of Group Investigation Learning Model toward social studies outcome in grade IV SDN Suko 1 Sidoarjo as 0,94. This study can be concluded that the Group Investigation learning model has a significant effect on social studies outcome at grade IV SDN Suko 1 Sidoarjo.